ISLAMICJERUSALEM UNDER MUSLIM RULE- A STUDY OF THE IMPLEMENTATION OF INCLUSIVE VISION ON THE REGION - Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2008)
This article examines some approaches needed to face the problems facing by Muslims in the context of Islamicjerusalem today. In discussing related issues, the author attempts to highlight historical facts, the current affairs of the region and Quranic perspective on justice and equality as the elements to achieve global peace. Apart from that, this article shows reflection on the future of this dispute region. The author comes with the hypothesis "there will be no peace and stability without justice.